Variations in the extracranial origin of the human vertebral artery - (:unkn) unknown (My University, 1989)
The aim of this study is to demonstrate a case of a cadaver in which both left and right vertebral arteries had an abnormal origin. On the left, the artery arose directly from the arch of the aorta. On the right, a double-originating vertebral artery was seen. The literature on the variations of the artery is reviewed and a detailed morphometric study of the artery was carried out because of its importance for neurosurgeons.
Keywords: Female; Humans; Middle Aged; Cadaver; Aorta, Thoracic; Vertebral Artery